THE SYNTHESIS OF CINNAMYL BENZOATE THROUGH ESTERIFICATION REACTION BETWEEN BENZOYL CHLORIDE AND CINNAMYL ALCOHOL REDUCED 96 FROM CINNAMALDEHYDE - Maghisya Oktanni; Cornelia - Budimarwanti (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2016)
This study was aimed at synthesizing cinnamyl benzoate through esteriﬁ cation reaction between benzoyl chloride and cinnamyl alcohol reduces from cinnamaldehyde. This study was started by reducing cinnamaldehyde to cinnamyl alcohol using NaBH4 reductor at room temperature. The reduction product of cinnamaldehyde was reacted using benzoyl chloride through esteriﬁ cation reaction using pyridine at room temperature for 4 hours. The product of cinnamaldehyde reduction and esteriﬁ cation reaction were characterized using TLC, IR spectrometer, and GCMS spectrometer.The results show that the reduction of cinnamladehyde produced yellow liquor that contain cinnamyl alcohol contained 81.31% and 63.94% randemen. While the result of esteriﬁ cation reaction between benzoyl chloride and cinnamyl alcohol produced brown liquor that contained cinnamyl benzoate contained 12.44% and 5.78% randemen.